Faculty Senate, Agenda, March 17, 2005 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2005)
Valdosta State University. Faculty Senate, Agenda, March 17, 2005.
1 electronic document. Faculty Senate, Agenda, March 17, 2005. 8 pages. 223,358 bytes.
Keywords: Valdosta State University. Faculty Senate; Electronic records; Committees; Corporation reports